Visualization of flow patterns during condensation in dimpled surface tubes of different materials. (November 2020) - Tang, Weiyu; Sun, Zhi-chuan; Li, Wei
Highlights: A new method for the measurement of the liquid height during stratified flows is developed and verified. The difference of flow patterns among two 1EHT tubes and the smooth tube is investigated. A flow pattern map for condensation in enhanced tubes is presented. Abstract: Flow patterns and their transitions during condensation of R410A inside two three-dimensional enhanced tubes and a plain tube were visualized and analyzed. Two three-dimensional enhanced tubes are made of stainless steel and copper, respectively, and their inner surfaces have an identical structure consisted of two different enhancement units. The primary enhancement unit refers to the helical dimples, while the background one is an array of petal-shaped dents on the external surface of tubes. The flow pattern visualizations were performed in the following test conditions: mass velocities 100–200 kg m −2 s −1, and vapor quality 0.1–0.9. Stratified, stratified-wavy, and annular flows were observed for the smooth tube, while another two flow patterns, including intermittent and semi-annular flow was seen for the enhanced tubes. The results indicated that the transition between annular flow to intermittent flow was shifted to a lower vapor quality for two novel enhanced tubes compared to the equivalent smooth tube. Besides, the void fraction under stratified and stratified-wavy flow was deduced by image processing and compared to some general correlations. A new void fraction model for enhanced tubes was proposed based on the present experimental results.